2022
DOI: 10.1021/acs.energyfuels.2c02286
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration of Olivine with Potassium- or Silicon-Rich Agricultural Residues Under Conditions Relevant to Dual Fluidized Bed Gasification

Abstract: The agglomeration characteristics of olivine-and potassium (K)-rich grape marc or silicon (Si)-rich wheat straw were studied in a laboratory-scale fluidized reactor and compared under air combustion, steam gasification, or CO 2 gasification atmospheres at temperatures relevant to a dual fluidized bed gasifier. Agglomeration with grape marc is found to be induced mostly by the formation of adhesive K-rich layers onto the olivine, a process that is significantly augmented in a steam atmosphere compared to that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 77 publications
(137 reference statements)
2
15
0
Order By: Relevance
“…Interestingly, it was observed from the SEM analyses performed on the cross-sections that continuous layers are unlikely to form on olivine sand. This implies that the addition of calcite may have inhibited the K-rich layer formation process, which has been reported for olivine sand without an additive due to the interactions between K-rich grape ash and olivine. For instance, the presence of a Ca-rich additive in the bed might have interfered with the substitution reactions that would otherwise occur between K + from grape marc and Mg 2+ /Fe 2+ from olivine.…”
Section: Resultsmentioning
confidence: 58%
See 4 more Smart Citations
“…Interestingly, it was observed from the SEM analyses performed on the cross-sections that continuous layers are unlikely to form on olivine sand. This implies that the addition of calcite may have inhibited the K-rich layer formation process, which has been reported for olivine sand without an additive due to the interactions between K-rich grape ash and olivine. For instance, the presence of a Ca-rich additive in the bed might have interfered with the substitution reactions that would otherwise occur between K + from grape marc and Mg 2+ /Fe 2+ from olivine.…”
Section: Resultsmentioning
confidence: 58%
“…This is also supported by the EDS point analysis performed on the layer that the atomic composition of Ca is 19% compared to 6% of K. The raw data of the EDS point analysis can be found in the Supporting Information (Table S1). Both Ca and K have been reported to react with olivine sand to form layers through ion-exchange reactions, , i.e., Ca 2+ or K + to substitute Mg 2+ /Fe 2+ in olivine. It has been suggested that statically Fe 2+ is likely to be replaced first before Mg 2+ is substituted .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations